The Influence of Celebrity Endorser and Brand Image on Rational Purchasing Decisions Scarlett Whitening With Consumer Trust as an Intervening Variable (Case Study of DKI Jakarta and DI Yogyakarta Students) - Rian Indra Wibowo; Lenny Christina Nawangsari; Gunardi Endro (PT FORMOSA CENDEKIA GLOBAL, 2024)
The development of free trade has created increasingly fierce business competition, which has encouraged companies to become more creative in carrying out their business activities. The market is characterized by various new products and services, with innovation continuing to develop. The company makes various efforts to increase sales, meet customer needs, and increase trust. Scarlett Whitening is a beauty product quite popular in Indonesia, as seen from its high sales figures, and it can beat foreign products. It is necessary to evaluate and improve several promotional efforts that have been carried out, such as those of celebrity endorsers and brand image, when faced with purchasing decisions and consumer trust as intervening variables. This research aims to determine the influence of Celebrity Endorsers and Brand Image on purchasing decisions, with consumer trust as an intervening variable. This type of research is quantitative. Data is presented through questionnaires distributed to 150 student representatives throughout Indonesia using the SEM PLS method for testing and hypothesizing. The results of this research show that there is no influence between celebrity endorsers and consumer trust and purchasing decisions.